Antioxidant Capacity and Microbial Attributes of Raw Cow Milk Fortified with Hypotrigona Squamuligera Honey (Global Journal of Medical Research, 2013)
Diseases such as diabetes, cancers, hypertension and obesity are problematic diseases in the adult population. The use of functional foods that consists of phytocompounds such as antioxidants that can act as prophylactics against such diseases has received considerable attention by the academia, food industry and the general public. The present study aimed at investigating antioxidant capacity and microbial attributes of cow milk fortified with Hypotrigona squamuligera honey. Antioxidant capacity was assayed using 2.2-diphenyl-1picrylhydrazyl (DPPH) antiradical activity and peroxide value method. Pour plate assay was used to investigate microbial attributes. The fortified milk revealed a significant DPPH antiradical activity than unfortified milk p > 0.05. A higher percentage inhibition of 98.38 ± 0.40 was achieved with fortified milk as compared to 47.27 ± 1.00. Fortified milk also exhibited significantly lower peroxide values and microbial attributes than unfortified milk. The present study results reveals that fortifying milk with H. squamuligera honey improves its antioxidant capacity and microbial inhibitory activity. This means that fortifying milk with H. squamulingera honey preserve milk and maintains its health promoting effects.
Keywords: antioxidant capacity; microbial attributes; hypotrigona squamuligera; fortified milk; honey